Discretionary Revenue and Ownership Structure: the Opportunistic View of Management - Istianingsih (International Journal of Advanced Science and Technology, 2020)
This study aims to examine whether the opportunistic behavior of management is influenced by firm characteristics and ownership structure. Management opportunism is measured by the discretionary revenue model from Stuben (2010), whilst the characteristics of companies that tested its impact on opportunistic management are auditor independence, firm size (size), leverage, growthownership structure is divided into two, institutional ownership and foreign ownership.The sample consists of 370 samples of the company during 2015-2017. Results show that the opportunistic management is significantly influenced by firm size and leverage. The larger firm has lower intention to perform management opportunism. Firm having higher debt level has larger motivation to engage in earnings management. Other results show that of the three ownership structure variables, only institutional ownership is proven to suppress opportunistic management attitude. Other variables, foreign ownership, auditor independence, and growth do not show a significant effect on management opportunistic attitude.